Anthocyanin Identification of Methanol-HCl Extract Active Fraction in Rosella (Hibiscus Sabdariffa. L) and Its Potential as Xanthine Oxidase Inhibitor - Pratiwi Puji Lestari; Dewi Kusrini; Khairul Anam (JURNAL SAINS DAN MATEMATIKA, 2014)
The active fraction of methanol-HCl extract of Roselle flower (Hibiscus sabdariffa. L) has been identified and its inhibitor xanthine oxidase potential tested. The aim of this study was to compare the inhibitory activity of xanthine oxidase from methanol-HCl extract and its fractionation results and to identify the chemical component of Roselle flower’s methanol-water active fraction which had xanthine oxidase inhibition activity. The chemical component identification of Roselle flower was preceded by extraction and fractionation. The types of chemical compound contents were identified by the spotting appearance, UV-Vis and IR spectroscopy. The quantification of chemical compound was carried out by TLC Scanner and xanthine oxidase inhibitory activity was tested in vitro. From this research, it was obtained the methanol-HCl extract yield of 4%. The Roselle methanol-HCl extract has the ability to inhibit activity of xanthine oxidase (IC50) was 0.64 ppm which was preponderant than the fractionation result. The 2nd fraction was the most active to inhibit the xanthine oxidase activity compared to the 1st and 3rd fraction. The main components of 2nd fraction were isolates A (Rf 0.9) and isolates D (Rf=0.64) which were expected as the group of anthocyanin. The relative level of isolate A and D were 4.67% and 24.24% respectively.